Desafios à prática notarial diante dos impactos da tecnologia Blockchain - Guimarães, Beatriz da Rosa (2024)
This Master's Dissertation aims to critically investigate the consequences of the adoption of blockchain technology by notary offices, focusing on the challenges that this innovation presents for the preservation of public faith, trust and legal certainty in the notarial context. This study also considers the impact of the Fifth Industrial Revolution, in order to better understand the interaction between technological innovation and traditional practices. Thus, the central problem of this research is: "in what way is blockchain redefining notarial practice in Brazil and, within this context, does this technology represent a threat to the preservation of legal certainty provided by notarial practice?". To answer this question, the first chapter aims to apply Niklas Luhmann's theory on trust, correlating it with the principle of legal certainty and the concept of public faith, in order to analyze the socioeconomic function of the Brazilian notary and its performance as a mechanism for reducing social complexity. The second examines the effects of the intersection between law and technology, using Niklas Luhmann's theory on the function and evolution of law, exploring the notion of technological autopoiesis from the perspective of Rafael Simioni, and analyzing the implications of the Fifth Industrial Revolution described by Marc Vidal. Both chapters provide an essential theoretical and conceptual basis for the subsequent analysis. The third and final chapter seeks to investigate the changes and impacts generated by the implementation of blockchain technology in notarial practice, using existing regulations as a reference. This analysis aims to identify potential risks that this technological innovation may present to notarial public faith, in addition to assessing the possible implications for trust and legal certainty. The hypothetical-deductive method was adopted, employing an exploratory and qualitative approach. The investigation was conducted through bibliographic research, with the organization and analysis of data facilitated by the indexing technique. At the end of the research, it was possible to confirm the following hypothesis: "the implementation of blockchain in notarial practice enhances efficiency and can significantly improve legal certainty by reinforcing pillars of notarial practice and adapting them to the digital age, representing more of an opportunity than a threat", given that there is a movement in the legal system towards integrating blockchain in a complementary way to the work of notaries and not as a substitute.